PENGARUH ASPEK LEKSIKAL DAN GRAMATIKAL DALAM MENGUATKAN PESAN PADA LAGU SATU BULAN BERNADYA - Maftuhatul Jannah; Rahma Aqila Putri (Jurnal Bastra (Bahasa dan Sastra), 2025)
This research was conducted to examine the lexical aspects and grammatical aspects of the song Satu Bulan sung by Bernadya using semantic studies. Lexical meaning and grammatical meaning are part of semantic studies which are generally found in a writing including song lyrics. Repetition and antonymy were found in the lexical aspect. Reference, substitution, detachment and conjunction in grammatical aspects.